Organic Materials Used for Giant Buddhas and Wall Paintings in Bamiyan, Afghanistan - Taniguchi, Yoko; Kawahara, Kazuki; Takashima, Miho; Cotte, Marine; Mazurek, Joy; Kumazawa, Yuki; Taga, Yuki; Nakazawa, Takashi (Applied sciences, 2022)
Since 2004, scientific research on the damaged Giant Buddha statues and Buddhist paintings in Bamiyan, Afghanistan, has been conducted at various laboratories and large-scale facilities using mass-spectrometry techniques (GC-MS, LC-MS, LC-MS/MS, nano-LC/ESI-MS/MS), ELISA, and synchrotron-based micro-analyses) in parallel to conservation intervention. Studies on samples from these cultural heritage objects have shown that each is composed of a polychromatic multilayered structure with sizing layers, ground layers, painted layers, and glaze. The carefully produced complex multilayered structures were examined using optical microscopy (visible and UV light) as well as synchrotron-based infrared microscopy, both of which revealed various organic and inorganic components in each layer. High sensitivity bulk MS and ELISA methods were used to further identify details regarding organic materials, such as fatty acids and collagens, and these results suggest different vegetable oils and animal species of glues. For example, cow milk casein and cow skin glue were identified in the Eastern Giant Buddha, suggesting that casein was used as a sizing agent and the cow skin glue as a binder for painting. The wall paintings from Cave N(a) (mid-7th century AD) were found to have horse glue used as sizing and drying oil (poppyseed/walnuts/perilla oils) as a binding media. The paintings’ complex structures and their organic and inorganic materials were fully understood using both imaging and bulk methods, and thus, these methods help to reconstruct historical wall painting techniques in full.